O componente curricular aspectos da vida cidadã (AVC) e o governamento de subjetividades - BRÍCIO, Vilma Nonato de (Universidade Federal do Pará, 2021)
This paper discusses the creation of the school curriculum, to analyze the emergency conditions of the curricular component aspects of Citizen Life (AVC) established by the School of Basic Education Agreement Scheme and Middle São Francisco Xavier that works in partnership arrangements between the Secretariat State of Pará State Education (SEDUC) and the Diocese of Abaetetuba in order to govern subjectivities. Set of school documents were analyzed, which it tracks some speeches about the invention of stroke and the ways became one of the legitimate spaces in the school to produce subjectivities governed.